Perlindungan Hukum Desain Industri dalam Inovasi Produk: Studi Kasus BirkinPet Harness Pada Era E-Commerce - Zafriana, Lusi; Nawangsari,, Ertien Rining; Nasution, Anita Hakim; Nasution, Arman Hakim; Saraswati, Rahaju (Jurnal Bisnis Indonesia, 2024)
This research aims to analyze the legal protection and regulatory aspects of the BirkinPet Harnessproduct innovation through a SWOT analysis approach, focusing on the role of industrial designprotection and regulations in maintaining competitiveness in the global market. The study employs anormative qualitative approach to examine relevant legal frameworks, combined with an empiricalapproach based on data related to the implementation of industrial design protection. The findingsindicate that BirkinPet’s key strength lies in its robust industrial design protection (score 1.350),granting exclusive rights to prevent imitation. However, weaknesses include the slow designregistration process in several countries (score 0.430) and inconsistent legal enforcement acrossvarious jurisdictions (score 0.705), which can hinder the protection of design rights.The primary opportunity lies in leveraging international agreements such as the Hague Agreement tofacilitate more efficient design protection across multiple countries (score 0.892). Furthermore,intellectual property protection features on e-commerce platforms provide an effective mechanism tocombat design infringements in the digital marketplace (score 0.816). The major threats identifiedinclude design infringements by international competitors (score 0.480) and emerging regulationsregarding pet product safety standards in various countries (score 0.450).This study concludes that strong industrial design protection, reinforced by international agreementsand e-commerce mechanisms, is essential for maintaining BirkinPet’s competitive advantage. Therecommendations include accelerating the design registration process and enhancing internationallegal enforcement to ensure more effective protection in the global market.Keywords: SWOT analysis, legal protection, industrial design, regulations, e-commerce.